Knowledge Management and Operational Capacity in Water Utilities, a Balance between Human Resources and Digital Maturity—The Case of AGS - João Faria Feliciano (MDPI AG, 2021)
Digitalization and knowledge management in the water sector, and their impacts on performance, greatly depend on two factors: human capacity and digital maturity. To understand the link between performance, human capacity, and digital maturity, six AGS water retail utilities were compared with all Portuguese utilities using Portuguese benchmark data (2011–2019). AGS utilities achieved better results, including in compound performance indicators, which are assumed to be surrogates for digital maturity. These compound indicators were also found to correlate positively with better performance. In fact, AGS utilities show levels of non-revenue water (NRW) (<25%) below the national median (30–40%), with network replacement values similar to the national median (<0.5%). These results seem to imply that higher digital maturity can offset relatively low network replacement levels and guarantee NRW levels below the national average. Furthermore, regarding personnel aging index and digital maturity—two internally developed indicators—there was an increase in the digital maturity and aging of the staff, which, again, raises questions about long-term sustainability. The growing performance and the slight increase in digital maturity can be attributed to group-wide capacity building and digitalization programs that bring together staff from all AGS utilities in year-long activities.